Effects of Genetics and Environment on Red Flour Beetle Aggregation - Toothaker, J. E.; Marshall, Jeremy (My University, 2018)
Red Flour Beetles are major pests for farmers storing grain and cause large profit losses. These beetles infest grain stores and their presence leads to mold growth (Baldwin). Learning the cause of aggregation groupings in Red Flour Beetles will help with pest control and would be a great step in the Nature versus Nurture Debate (Breed). Males produce a pheromone to attract females that seems to influence social behaviors (Boake). The effects genetics and environment have on aggregation behaviors of Arkansas and Brazilian strains have never been evaluated. This project was designed to fill this research gap by assessing the impacts of genetics and environment on aggregation groupings of Arkansas and Brazilian strains of Red Beetles. The results of the study show that environment has the largest influence on groupings on the first day, but then genetics has the largest influence in the days following. This leads to the implication that genetics has a deeper effect on aggregation than environment overall; but environment has a stronger effect for a short amount of time.
Keywords: Fall 2018